Unstable Transgene Expression Affects Long-Term Efficacy of the Arabidopsis Immune Receptor EFR to Confer Quantitative Resistance to Citrus Canker Under Field Conditions - Mukesh Jain; Gerald V. Minsavage; Naweena Thapa; Diana M. Horvath; Cyril Zipfel; Gloria A. Moore; Latanya C. Fisher; Vladimir Orbović; Jeffrey B. Jones (PhytoFrontiers)
The Arabidopsis thaliana pattern recognition ELONGATION FACTOR-TU RECEPTOR (EFR) recognizes and binds the bacterial pathogen-associated molecular pattern (PAMP) elongation factor thermo unstable (EF-Tu) and its highly conserved derived peptide elf18. Previous work revealed that the transgenic expression of EFR (and chimeric EFR::XA21) in several heterologous plant species, including in members of Solanaceae and in sweet orange, confers broad-spectrum bacterial disease resistance. In this study, stable sweet orange (Citrus × sinensis) and grapefruit (Citrus × paradisi) transformants expressing EFR or EFR::XA21 were generated in an attempt to confer broad spectrum resistance to Xanthomonas citri subsp. citri (Xcc), the causal agent of citrus canker, a serious disease of commercial citriculture. The transgene expression was confirmed via real-time quantitative reverse transcriptase PCR (RT-qPCR). Juvenile transgenic trees were challenged with Xcc (spray and pinprick inoculation) and evaluated for canker susceptibility and disease progression. Three independently transformed transgenic events (out of 19 total) displayed partial resistance to canker when spray-inoculated, and one line showed resistance when wound-inoculated. Surprisingly, when two mature transgenic lines were evaluated under field conditions and exposure to natural infection, both were found to be as susceptible as the wild-type under prevalent pathogen load. RT-qPCR data indicated a gradual decline and significant spatial variability in EFR expression in leaves excised from different branches of the same tree. The data presented here call for a need for evaluating different promoters for stable and long-term EFR expression in woody perennial species. [Figure: see text] Copyright © 2024 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.